2010
DOI: 10.1534/genetics.110.116293
|View full text |Cite
|
Sign up to set email alerts
|

Genes Required for Cellular UNC-6/Netrin Localization in Caenorhabditis elegans

Abstract: UNC-6/Netrin is an evolutionarily conserved, secretory axon guidance molecule. In Caenorhabditis elegans, UNC-6 provides positional information to the axons of developing neurons, probably by establishing a concentration gradient from the ventral to the dorsal side of the animal. Although the proper localization of UNC-6 is important for accurate neuronal network formation, little is known about how its localization is regulated. Here, to examine the localization mechanism for UNC-6, we generated C. elegans ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 88 publications
2
31
0
Order By: Relevance
“…We found that unc-17(e245), unc-104(e1265), or cha-1(p1152) enhances the AVM ventral axon guidance defect caused by slt-1(eh15), which suggests that acetylcholine potentiates UNC-6-mediated axon guidance ( Figure 2D). Our results are similar to those previously reported for unc-104(e1265) (Asakura et al 2010).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We found that unc-17(e245), unc-104(e1265), or cha-1(p1152) enhances the AVM ventral axon guidance defect caused by slt-1(eh15), which suggests that acetylcholine potentiates UNC-6-mediated axon guidance ( Figure 2D). Our results are similar to those previously reported for unc-104(e1265) (Asakura et al 2010).…”
Section: Resultssupporting
confidence: 93%
“…In fact, a recent study provides evidence that UNC-104 might be required for UNC-6 secretion (Asakura et al 2010). In this study, a Venus-tagged UNC-6 showed a punctate distribution pattern throughout the cytoplasm and axons of wild-type neurons, but in unc-104 (e1265) mutants the UNC-6 was observed evenly distributed in the cell body with little detected in the axon.…”
Section: Resultsmentioning
confidence: 55%
“…5A-C; P<0.0001), suggesting that only a small fraction of TIR-l was localized to puncta in the AWC axons in unc-104(e1265) mutants compared with wild type. Unlike synaptic vesicles, dense core vesicles and UNC-6/netrin [which were shown to accumulate in the cell body and dendrites of unc-104 mutants (Asakura et al, 2010;Hall and Hedgecock, 1991;Nonet, 1999;Ou et al, 2010;Zahn et al, 2004)], TIR-1 was not detected in the AWC cell body or dendrites in unc-104 mutants. These results suggest that unc-104 may be required for the stability of TIR-1 protein, similar to the function of kinesin KIF4 in regulating intracellular trafficking and stability of HIV-1 Gag polyprotein (Martinez et al, 2008).…”
Section: Research Articlementioning
confidence: 97%
“…1c). Therefore, previous screens that identified mutants focusing on one trait (such as synaptic localization)5657, or based on qualitative inspection, must have relied on favourable sampling of these populations (either by having screened more than one animal from these genotypes or by having stochastically sampled a phenotypically severe individual); in other words, many alleles could have been missed in these screens, and even in the screens for severe phenotypic changes.…”
Section: Resultsmentioning
confidence: 99%